THE IMPORTANCE OF THE HUMAN AND SOCIAL SCIENCES IN THE UNDERGRADUATE COURSE IN NUTRITION: AN EXPERIENCE REPORT - Romilda de Souza Lima (Universidade do Estado do Rio de Janeiro, 2017)
In this essay, a report of experience, a brief discussion is presented on the contribution of the social sciences to the study of Nutrition. It also presents the experience as a teacher in two disciplines offered for the undergraduate course in Nutrition at a state public university in Paraná: Food Anthropology and Sociology Applied to Nutrition. The focus is on the contribution to think, in a multidisciplinary and interdisciplinary perspective, the curricular grade of the course. The positions of some authors of the social sciences, including those of Sociology and Food Anthropology, are presented. As an experiment, it is reported how the subjects have been conducted, the challenges and the perceived changes in the students regarding the importance of these contents in the academic formation, and how it is possible to observe the adoption of this knowledge in the activities of research and extension by the / of the students of said course. In spite of its reduced hours (68 hours / year for each subject), it is noticed that the contents developed in the classroom have contributed to broaden the view of the students when studying contents that help them understand the social, cultural and political aspects of food and nutrition. DOI:10.12957/demetra.2017.28626